2016
DOI: 10.1111/pbi.12647
|View full text |Cite
|
Sign up to set email alerts
|

The durable wheat disease resistance gene Lr34 confers common rust and northern corn leaf blight resistance in maize

Abstract: SummaryMaize (corn) is one of the most widely grown cereal crops globally. Fungal diseases of maize cause significant economic damage by reducing maize yields and by increasing input costs for disease management. The most sustainable control of maize diseases is through the release and planting of maize cultivars with durable disease resistance. The wheat gene Lr34 provides durable and partial field resistance against multiple fungal diseases of wheat, including three wheat rust pathogens and wheat powdery mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 71 publications
(105 reference statements)
0
55
0
1
Order By: Relevance
“…[5] In contrast to wheat, where Lr34 is only expressed at adult plant stage, barley and rice already showed Lr34 resistance at seedling stage. Therefore, transgenic barley and rice plants offered a valuable tool to study the molecular differences in pathogen resistance caused by Lr34.…”
Section: Introductionmentioning
confidence: 98%
“…[5] In contrast to wheat, where Lr34 is only expressed at adult plant stage, barley and rice already showed Lr34 resistance at seedling stage. Therefore, transgenic barley and rice plants offered a valuable tool to study the molecular differences in pathogen resistance caused by Lr34.…”
Section: Introductionmentioning
confidence: 98%
“…All resistant wheat cultivars carry the same Lr34 allele ( Lr34res ) that evolved from an ancestral, susceptible allele ( Lr34sus ) after wheat domestication by two gain‐of‐function mutations (Krattinger et al ., ). Lr34res is functionally transferrable into all major cereals as a transgene, including barley ( Hordeum vulgare ), rice ( Oryza sativa ), maize ( Zea mays ), and sorghum ( Sorghum bicolor ) (Risk et al ., ; Krattinger et al ., ; Sucher et al ., ; Schnippenkoetter et al ., ; Boni et al ., ). In these cereal species, Lr34res resulted in enhanced resistance against various biotrophic or hemi‐biotrophic fungal pathogens, as well as in the development of LTN.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, disease development was slower and pathogen growth reduced on Lr34 ‐transgenic plants, as already described by using chitin quantification (Boni et al ., ). This has also been reported for various other fungal pathogens such as M. oryzae and Puccinia sorghi in transgenic Lr34 rice (Krattinger et al ., ) and maize (Sucher et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Sucher et al . () have also suggested that the resistance could occur during the prehaustorium or feeding structure formation stage; this is the infection step common to both biotrophic and hemibiotrophic pathogens affected by Lr34 . Rubiales & Niks () showed that the reduction of infection frequency and the increase of latency period provided by Lr34 was associated with a reduction of haustorium formation and a lower rate of intercellular hyphal development.…”
Section: Discussionmentioning
confidence: 99%